1979
DOI: 10.1288/00005537-197906000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Orbital‐facial complications of sinusitis in children

Abstract: Although complications of sinusitis in children have lessened remarkably since and advent of antibiotics, nevertheless they still occur. In a 25-year period at the Hospital for Sick Children, 6,770 patients with the diagnosis of sinusitis were reviewed and 159 of these had orbital-facial complications. Surgical intervention was necessary in 17 to prevent more serious complications. Although there were no deaths in non-malignant disease, two patients developed permanent optic atrophy, presumably because of dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 1 publication
5
27
1
1
Order By: Relevance
“…In contrast to most reported series, Mortimore&Wormald, 1997 Moloney et al, 1987, , Spires&Smith, 1986, Fearon et al, 1979, we had more adults (n=19 / %) than children (n=11 / %).…”
Section: Prevalencecontrasting
confidence: 83%
“…In contrast to most reported series, Mortimore&Wormald, 1997 Moloney et al, 1987, , Spires&Smith, 1986, Fearon et al, 1979, we had more adults (n=19 / %) than children (n=11 / %).…”
Section: Prevalencecontrasting
confidence: 83%
“…The predisposing factor for the orbital cellulitis was acute sinusitis which was confirmed by many authors. Fearon et al [4] suggested that complicating sinusitis is commoner in the younger age group because vascular development is greater, with softer and more diploeic bone that allows infection to spread with greater ease.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective multi-institutional study found intracranial complications in only 3.7% of hospital admissions for acute or chronic sinusitis. 5) The diagnosis requires a high index of suspicion and confirmation by imaging. 6) Septic thrombophlebitis of the cavernous sinuses secondary to paranasal sinusitis is extremely rare.…”
Section: Discussionmentioning
confidence: 99%